1997
DOI: 10.1046/j.1365-2141.1997.2153034.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus associated B‐cell lymphoma after autologous bone marrow transplantation for T‐cell acute lymphoblastic leukaemia

Abstract: Summary. Epstein-Barr virus associated lymphoproliferative disease after autologous bone marrow transplantation (ABMT) has rarely been reported. We report a case of Bcell lymphoma following ABMT for T-acute lymphoblastic leukaemia; bone marrow was purged in vitro with monoclonal antibodies to remove T cells. Immunoglobulin and T-cell receptor gene rearrangement studies were used to demonstrate clonality and to show that this patient developed a second neoplasm after ABMT. EBV proteins and genome (type A) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…One of the EBVseropositive patients developed a post-transplant lymphoproliferative disease after a T cell depleted CD34 + selected autologous stem cell transplantation for systemic lupus erythematodes. Although the risk of EBV post-transplant lymphoproliferative disease after autologous transplantation is low, case reports of this complication in the autologous setting exist [Chao et al, 1993, Briz et al, 1997, Hauke et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…One of the EBVseropositive patients developed a post-transplant lymphoproliferative disease after a T cell depleted CD34 + selected autologous stem cell transplantation for systemic lupus erythematodes. Although the risk of EBV post-transplant lymphoproliferative disease after autologous transplantation is low, case reports of this complication in the autologous setting exist [Chao et al, 1993, Briz et al, 1997, Hauke et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] However, it should be noted that, although the majority of cases occur in such high-risk patients, there are reports of PTLD even after autologous BMT. [16][17][18] In our eight cases, the pathology was either DLBC lymphoma (five) or PBCH (three). The six patients with disseminated disease were equally grouped between DLBC lymphoma and PBCH.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the TCR gene rearrangement is not clear, however, it has been well reported. 8,13 Perhaps the presence of both IgH and TCR gene rearrangements indicate oligoclonality, and therefore a better prognosis than monoclonal changes. In our patients, the early presentation of PTLD post ASCT may partially explain the favorable response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the seven reported cases of PTLD after ASCT were treated with corticosteroids and the only patient who survived also had therapy with acyclovir and IFN. 5,8,11 IFN has been shown to reduce EBV-induced B cell proliferation, and has been successfully used in other hematologic malignancies. 17 Shapiro et al 18 reported the first cases of IFN for B cell lymphoproliferative disorders (two post BMT), with dramatic responses to IFN and IVIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation